Nuclear Magnetic Resonance Spectroscopy for Medical and Dental Applications: A Comprehensive Review - Zia, Komal; Siddiqui, Talal; Ali, Saqib; Farooq, Imran; Zafar, Muhammad Sohail; Khurshid, Zohaib (European Journal of Dentistry, 2019)
Nuclear magnetic resonance (NMR) spectroscopy is one of the most significant analytical techniques that has been developed in the past few decades. A broad range of biological and nonbiological applications ranging from an individual cell to organs and tissues has been investigated through NMR. Various aspects of this technique are still under research, and many functions of the NMR are still pending a better understanding and acknowledgment. Therefore, this review is aimed at providing a general overview of the main principles, types of this technique, and the advantages and disadvantages of NMR spectroscopy. In addition, an insight into the current uses of NMR in the field of medicine and dentistry and ongoing developments of NMR spectroscopy for future applications has been discussed.
Keywords: dentistry; metabolism; multiple sclerosis; spectroscopy